Analysis of different tracking intervals for Parabolic Trough Collectors for water disinfestation in agricultural applications - Paulo Alexandre Costa Rocha; Stéphano Praxedes Mendonça; Thiago Taketaro Guilherme Watanabe; Maria Eugênia Vieira da Silva; Ricardo José Pontes Lima (Semina: Ciências Agrárias, 2020)
The use of renewable energy is growing every year as an alternative to fossil fuel technology. Solar energy presents itself as a good alternative due to its great availability and energy potential. Solar thermal energy uses heat to warm fluids, and can also generate electricity, as well as being used in industrial processes and water desalination. The research and use of Parabolic Trough Collectors (PTCs) has been growing in recent years due to their ability to heat fluids at high temperatures in a relatively small area. In this work, two small PTCs were manufactured and tests were performed to improve the arrangements in order to increase the absorbed energy to reach temperature values for water disinfestation, aiming at the control of phytopathogens to control soil pathogens in small and medium farms. To control the automatic tracker, a low-cost system with Arduino, Light Dependent Resistors (LDRs) and step motors was used. The tracking times intervals analyzed were 1, 5 and 15 minutes. For the 1-minute tracking interval, the PTCs presented a thermal efficiency of 25.87%, with temperatures between 45 and 70 °C and an average of 63.73 °C. For the 5-minute tracking interval, the thermal efficiency was 18.48%, reaching temperatures between 41 and 68 °C and an average of 57.9 °C. For the 15-minute tracking interval, the PTCs presented a thermal efficiency of 14.80%, with temperatures between 39 and 62 °C and an average of 51.88 °C. The results showed that the tracking intervals of 1 and 5 minutes present more values between the lethal temperature range of 45 and 60 °C for phytopathogens. For agricultural application, the usage of a tracking interval of 5 minutes could be a good option for reducing the waste of system energy compared to the interval of 1 minute.